Association of socio-demographic characteristics, comorbidities, lifestyle habits, and saliva parameters with dental caries in adults with obesity - Virginie Chuy; Marie Mayoute; Maud Monsaingeon-Henry; Blandine Gatta-Cherifi; Élise Arrivé (Acta Odontologica Scandinavica)
Objective: To describe the oral health status of patients with obesity and to explore the socio-demographic characteristics, comorbidities, lifestyle habits (tobacco, alcohol, sweet/acidic diet), and saliva parameters most associated with the dental caries experience.